Trade liberalization during transition: A political economy perspective - Norbert Wunner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
Most transitional economies in Central and Eastern Europe have rather surprisingly resisted protectionist pressures - at least during early stages of reform - and adopted liberal trade policies. In this paper the course of trade policy during transition is explained from a political economy perspective. It is shown that trade liberalization can be a rational strategy of reform politicians maximizing the probability of electoral success. In this context it is also discussed how trade policy affects the restructuring of state firms, i.e. their transformation into private firms. It is shown that less protection of the state sector does not necessarily enhance restructuring.
Keywords: D72; F13; P21; 330; Trade Policy; Transition; Probabilistic Voting; Handelsliberalisierung; Übergangswirtschaft; Neue politische Ökonomie; Organisatorischer Wandel; Theorie